Skin Cancer Knowledge, Attitudes, and Practices among Chinese Population: A Narrative Review - Philip M. Stephens; Brian Martin; Ghazal Ghafari; James Luong; Vinayak K. Nahar; Linda Pham; Jiangxia Luo; Marcelle Savoy; Manoj Sharma (Dermatology Research and Practice)
Skin cancers are becoming a substantial public health problem in China. Fair skin and increased exposure to ultraviolet B (UVB) rays from the sun are among the most substantial risk factors for skin cancer development, thus making the Chinese people vulnerable to this group of diseases. The purpose of this article is to present a narrative review of the knowledge, attitudes, and practices (KAP) related to skin cancers within the Chinese population. A systematic electronic search of MEDLINE (PubMed), CINAHL, ScienceDirect, and Google Scholar databases yielded nine articles that met the inclusion criteria. The review found that although sunscreen application was a commonly used method of skin protection among the general Chinese population, educational interventions enhancing current knowledge and attitudes about the effects of UVB rays on skin from undue sun exposure were limited in many smaller communities of the country. Hence, there is an essential need to design effective, evidence-based educational programs promoting sun protection behaviors in both congregated and sparsely populated areas of China.